Austria : Financial System Stability Assessment-Press Release; Staff Report; and Statement by the Executive Director for Austria. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2020)
This paper presents Austria's 2019 Financial System Stability Assessment. The Austrian authorities have proactively strengthened the financial stability framework since the previous Financial Sector Assessment Program (FSAP). The FSAP analysis suggests that banks are, in aggregate, resilient to severe macrofinancial shocks, although most banks would make use of capital conservation buffers. Mutual financial cooperation arrangements among banks act as a shock absorber for idiosyncratic shocks, but high financial interlinkages may fuel loss propagation in a systemic event. While a robust regulatory framework and prudential policy actions have lowered financial stability risks, challenges include data and regulatory gaps, resource constraints, high interconnectedness, and exposure to cross-border and money-laundering risks. Authorities should enhance monitoring and oversight related to contagion/spill over risks. This would include enhancing the stress testing framework to consider second round effects and contagion, improving data collection on foreign exposures, nonfinancial corporates and real estate, and strengthening supervision of related party, group-wide, and money-laundering risks. Supervisors should be able to take timely action and correct unsustainable risk taking, including unsustainable lending and business models.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet